PROSEDUR ATAS PEMBERIAN KREDIT PADA KOPERASI SIMPAN PINJAM (KSP) BERKAT ARTHA SENTOSA - Syabina Putri Susanti; Masripah Masripah (Fakultas Ekonomi Dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2022)
The problem of poorness is not a new problem in Indonesia. The government has tried various ways to solve this problem, one of which is by establishing cooperatives. There are various types of cooperatives in Indonesia, ranging from consumer cooperatives, producer cooperatives, service cooperatives, multi-business cooperatives, and savings and loan cooperatives. Berkat Artha Sentosa Saving and Loan Coorporative is one of the cooperatives that provides savings and loan services. This cooperative aims to help improve the economic welfare of its members by making savings and providing loans or credits. The purpose of this research is to find out the procedure for granting credit and find out the right solution in dealing with non-performing loans. Every activity carried out by cooperatives, of course, has a Standard Operating Procedure in order to harmonize and achieve the goals to be achieved. Likewise with lending activities. The procedure includes the stages of applying for credit, receiving loan documents, issuing loan approval memos, disbursing loans, and paying off loans. Even though the cooperative already has a well structured procedure, it does not make the cooperative far from default, such as bad credit. In overcoming these problems, the cooperative has a solution by providing relief by increasing the payment period and offering restructuring.Kata Kunci: Procedure, Saving and Loan Cooperative, Non-Performing Loan AbstrakAdapun tujuan dilakukannya penelitian ini guna untuk mengetahui prosedur pemberian kredit dan mengetahui solusi yang tepat dalam menghadapi kredit bermasalah. Setiap kegiatan yang dilakukan oleh koperasi, tentunya memiliki Standar Operasional Prosedur guna selarasnya dan tercapainya tujuan yang ingin dicapai. Begitu pula dengan kegiatan pemberian kredit. Dalam prosedurnya, mencakup tahapan permohonan pemberian kredit, penerimaan dokumen pinjaman, penerbitan memo persetujuan pinjaman, pencairan pinjaman, dan pelunasan pinjaman. Walaupun koperasi sudah mempunyai prosedur yang tersusun dengan baik, tidak membuat koperasi jauh dari wanprestasi, seperti kredit macet. Dalam mengatasi permasalahan tersebut, koperasi mempunyai solusi dengan pemberian keringanan dengan menambahkan jangka waktu pembayaran serta menawarkan restrukturisasi. Keywords: Prosedur, Koperasi Simpan Pinjam, Kredit Bermasalah